In vitro allelopathic potential of Photinia × fraseri extracts on the seed germination of selected crop and weed species (Bioscience Journal, 2025)
In sustainable agriculture, allelopathy emerges as a promising strategy for eco-friendly weed management. This study provides a preliminary in vitro assessment of the allelopathic effects of aqueous flower and leaf extracts of Photinia × fraseri on the seed germination of selected crop (wheat, corn, lentil, lettuce) and weed (radish, purslane) species. The chemical composition of the extracts was analyzed using GC-MS, and germination assays were conducted at five concentrations: 1%, 25%, 50%, 75%, and 100%, corresponding to 0.5, 12.5, 25, 37.5, and 50 mg ml−1, respectively. The results showed a concentration-dependent inhibition of germination in all tested species, with flower extracts exhibiting higher allelopathic effects than leaf extracts. Lettuce and radish seeds were the most sensitive, while corn and wheat were the least affected. Given that wild radish is a common agricultural weed, flower extract concentrations of 50% and above may represent potential candidates for bioherbicide development. These findings are an initial step toward understanding the allelopathic potential of P. × fraseri, and further in vivo pot and/or field studies are recommended to validate its practical applicability.